Northern Hemisphere Rossby Wave Initiation Events on the Extratropical Jet—A Climatological Analysis - Röthlisberger, Matthias; Martius, Olivia; Wernli, Heini (Journal of Climate, 2018)
A climatology of Rossby wave initiation (RWI) events on the Northern Hemisphere midlatitude jet is compiled by applying an objective RWI identification algorithm to the ERA-Interim dataset. In winter, RWI events occur most frequently over the northwestern Pacific and less often over the North Atlantic. In summer, the total number of RWI events is lower than in winter and the North Pacific RWI region shifts toward the Tibetan Plateau. Composite analysis of the large-scale flow prior to, during, and after winter North Pacific RWI events shows an upstream wave train propagating across Asia on the Arctic waveguide prior to RWI. The composite wave forms on a relatively weak zonal jet streak, exhibits a baroclinic structure, and is strongly amplified by latent heat release in the warm conveyor belt of a deepening surface cyclone. Moreover, the wave forms in a region of large-scale upper-level deformation, upstream of a preexisting ridge. Further, active tropical convection affects the longitude where RWI occurs and thus acts as a geographical anchor for RWI. Individual RWI events are characterized by preferred combinations of these composite features: a strong surface cyclone tends to occur in concert with strong latent heating and a pronounced positive PV anomaly aloft. A second group of co-occurring features contains active tropical convection, a strengthened subtropical anticyclone, and the downstream ridge. These feature groups might be regarded as idealized archetypal RWI scenarios, although numerous intermediate events exist where features from both groups occur together.